Investigation of potential use of by-products from cold-press industry as natural fat replacers and functional ingredients in a low-fat salad dressing - Tekin-Cakmak, Zeynep Hazal; Karasu, Salih; Kayacan-Cakmakoglu, Selma; Akman, Perihan Kubra (WILEY, 2021)
In this study, the physicochemical, bioactive, antimicrobial, and fat replacer properties of by-products (black cumin seed [BOB], coconut [COB], flaxseed [FOB], and pumpkin seed [POB]) from the cold-press oil industry were investigated. The by-products were rich in protein, carbohydrate, and fiber contents. TPC (total phenolic content), CUPRAC (cupric reducing antioxidant capacity) values, in vitro bioaccessibility of phenolic compounds, and phenolic profile were analyzed to determine bioactive properties of by-products. FOB and BOB showed higher TPC and CUPRAC values and a higher antimicrobial effect, while phenolic compound diversity compared to other samples; therefore, they can be considered good bioactive sources. The steady and frequency sweep test rheological properties were conducted to determine the potential use of selected by-products as a fat replacer in low-fat salad dressing. The salad dressing samples enriched with by-products showed strong pseudoplastic and solid-like characteristics, except when enriched with 1% FOB and POB. This study suggests that by-products can be used in low-fat salad dressing as natural fat substitutes and functional ingredients. Novelty impact statement Cold-press oil processing results in a byproduct rich in protein, carbohydrate, and bioactive components. These by-products are suitable for food application, as no chemical treatment, such as solvent application, is applied during cold-press processing. The most important problem in the production of low-fat salad dressing is the less compact structure resulting from the reduction of fat. Protein- and carbohydrate-rich ingredients are used for the development of this structure. In addition, salad dressings are poor food groups in terms of bioactive components, and their bioactive properties should be improved. In this study, the comprehensive physicochemical and bioactive characterization, and potential use of these by-products in low-fat salad dressing as fat replacers were firstly investigated.
Keywords: BLACK CUMIN; ANTIOXIDANT CAPACITY; PHENOLIC-COMPOUNDS; TOMATO POMACE; SEED; L.; EMULSIONS; MAYONNAISE; TOCOPHEROL; STABILITY; Food Science & Technology